Thermal Degradation Kinetics of Modified Fe3O4 With Poly(Vinyl Chloride) via Click Chemistry - Tukur, Abdulrahman; Pekdemir, Mustafa Ersin; Abubakar, Abdullahi Musa (Turkish Chemical Society, 2023)
The PVC-g-poly(POHMAC-co-VTM)-g-Fe3O4 and its precursors were characterized based on thermal properties comprising the initial decomposition and final decomposition temperatures and the maximum decomposition rate temperature were studied by TG/DTG and the decomposition steps were investigated. Then, the thermal characteristics of the final product formed via click chemistry, PVC-g-poly(POHMAC-co-VTM)-g-Fe3O4 were evaluated through thermogravimetric analysis (TGA) under argon atmosphere at 5, 10, and 15 °C/min. The studied temperature selection is 0 to 800 °C. Centered on the iso-conversional method, the thermal degradation kinetic parameter of the energy of activation was computed by the free model methods of the Flynn-Wall-Ozawa method (FWO) and Kissinger-Akahira-Sinuse method (KAS). The predicted activation energy values ranged from 41.40 to 117.83 KJ/mol meanwhile the average energy of activation values were computed as 85.75 KJ/mol and 72.31 KJ/mol respectively for the FWO method and KAS method. In addition, a saturation magnetization of 33.7 emu/g was recorded using vibration sample magnetometer (VSM). © 2023, Turkish Chemical Society. All rights reserved.
Keywords: Click chemistry; Fe3O4; Kinetics; PVC; Thermal degradation